Psychology Biases Explanation On Malaysian Day Of The Week Anomaly - Brahmana, Rayenda Khresna (2013)
The main assumption in conventional finance is rational behavior. Based on this tenet, investor is presumed cannot beat the market because each investor has same amount of information with similar quality. However, market anomalies, such as Day-of-the week anomaly, are the dossiers to show that basic tenet cannot be longer hold. Considering the importance of DOWA in investment strategy and finance theory, it is imperative to study further the determinant of that Monday irrationality from the perspective of investor’s behavior. Even though many researchers have proposed trading behavior as the explanation of the Monday Irrationality or Day-of-the Week anomaly, yet, it has still left without empirical evidence. This research aims to investigate empirically by gauging psychological approach whereas the affection bias (weather-induced mood, and moon-induced mood), and cognition bias (attention bias, and cognitive dissonance) are the factors. In regards of examining the relationships, this study employed two regression models, namely, interactive model and day-by-day model. Preceding this phase, the role of affection (temperature and full moon) was preliminary tested by conducting time series quasi experimental study.